The Effect of Sweet Potatoes Leaves (Ipomoea batatas) on Blood Profile and Survival Rate of Tilapia (Oreochromis niloticus) - Nur Fajriani Nursida; Tri Widayati Putri (Faculty of Agriculture Musamus University, 2020)
In aquaculture, fish health problems are often encountered which can lead to failure in cultivation activities. One of the efforts to overcome the problem of disease in cultivation is done by providing immunostimulants. Sweet potato leaves (Ipomoea batatas) are plants that have a short harvest period, cheap and rich in vitamins and antioxidants so that it can be used as a source of immunstimulants. This research was conducted to determine the effect of adding sweet potato leaves (Ipomea batats) to tilapia (Oreochromis niloticus) feed on total leukocytes, phagocytic activity, hematocrit, and survival rate. The study was conducted by experimental method using a completely randomized design, with 4 treatment doses of sweet potato (Ipomoea batatas) used were 0%, 5%, 10% and 15%, which were formulated in fish feed and each treatment was repeated 3 times.. The results showed that giving 10% of sweet potato (Ipomea batatas) leaves in feed had a significant effect on the non-specific immune system of tilapia, which could increase the highest total leukocyte value by 6600 mm3 but did not have a significant effect on the phagocytosis index. 96.3%, 31% hematocrit with 93% survival.